OTORITAS JASA KEUANGAN DAN PENGAWASAN TERHADAP PERBANKAN SYARIAH DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Noranisa, Noranisa; Ilyas, Musyfikah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to determine the supervision system of the Otoritas Jasa Keuangan in Sharia Banking according to Law Number 21 of 2011. The type of research used is literature with a syar'i juridical approach. Data sources are primary and secondary data. The results showed that supervision of Islamic banking is carried out by 2 (two) authorities, internally carried out by the Dewan Pengawas Syariah (DPS) or Dewan Syariah Nasional (DSN) and the Otoritas Jasa Keuangan is an external supervisor. In carrying out its duties, the Otoritas Jasa Keuangan is authorized to assess islamic banking operations both off site and on site. In Islamic law, the function of the Otoritas Jasa Keuangan is the same as that of al-Muraqabah, so that the position of the Otoritas Jasa Keuangan can be changed with the al-Hisbah institution which functioned as a market controller in the time of the Prophet Muhammad saw.